Egyptian audience's perception of political satire show: an analysis of the perceived and actual influence of political comedy programming - Younis, Dina Mohamed (AUC Knowledge Fountain, 2014)
As more Egyptians continue to expose themselves to the political comedy program Al Bernameg, scholars should seek to understand the audience’s perception of the program. This study examines the perception of the Egyptian audience on the political satire show Al Bernameg. The study aims at measuring the perceived bias of Al Bernameg and the perceived and actual influence of the program. This study seeks to explore the influence Al Bernameg has on its audience in relating it to the Third Person effect theory. It examines the difference between the actual purpose for watching Al Bernameg and the perceived purpose. The study employed survey research as its primary source of data collection to investigate the research hypothesis via a purposive sample of 508 Egyptians. The research findings revealed a significant third-person effect pattern for the political satire program, especially among younger viewers